RISIKO PERILAKU SEDENTARI TERHADAP OBESITAS PADA REMAJA PUTRI KOTA MAKASSAR - Hermawati Hamalding; Mohammad Basri (Pascasarjana Universitas Negeri Makassar, 2022)
This study aims to assess the risk of sedentary behavior to obesity in young women in Makassar , this research is an observational study with a cross-sectional study approach, the variables studied in this study are physical activity, TV viewing habits and the habit of using a gadget on obesity in female adolescents. , a total sample of 67 samples was taken using a proportional stratified random sampling technique using a measurement questionnaire by WHO's Antro Plus. Data processing and analysis used the chi square statistical test. The results showed that there was a significant relationship between physical activity and obesity with a p value (0.012) < 0.05, the habit of watching TV has a p value (0.031) > 0.05 and the use of gedjet has a p value (0.031) < 0.05. This shows that there is a significant relationship between sedentary behavior and the risk of obesity in young women so that it is hoped that young women can make changes from negative behavior to positive behavior.